Imprint of Trace Dissolved Oxygen on Prokaryoplankton Community Structure in an Oxygen Minimum Zone - Medina Faull, Luis; Mara, Paraskevi; Taylor, Gordon T.; Edgcomb, Virginia P. (Frontiers in Marine Science, 2020)
The Eastern Tropical North Pacific (ETNP) is a large, persistent, and intensifying oxygen minimum zone (OMZ) that accounts for almost half of the total area of global OMZs. Within the OMZ core (~350-700 m depth), dissolved oxygen is typically near or below the analytical detection limit. Steep oxygen gradients above and below the OMZ core lead to vertical structuring of microbial communities that also vary between particle-associated (PA) and free-living (FL) size fractions. Here, we use 16S amplicon sequencing (iTags) coupled with multivariate statistics to analyze the diversity and distribution of prokaryotic populations between FL and PA size fractions and among the range of existing redox conditions. Nonmetric Dimensional Scaling (nMDS) revealed that bacterial and archaeal phylogenetic representations were significantly different between size fractions. Based on analysis of similarities (ANOSIM) and iTag profiles, composition of PA assemblages was less influenced by the prevalent depth-dependent biogeochemical regime than the FL fraction. Trace oxygen concentrations (~0.33 M) were present throughout the OMZ core at our sampling location. Consequently, nitrite accumulations typically reported for OMZ cores were absent. Furthermore, sequences for anammox bacteria (Brocadiales genus Candidatus Scalindua), commonly found at oxic-anoxic boundaries in other systems, were not recovered here. However, ammonia-oxidizing bacteria (AOB) and archaea (AOA) distributions and maximal autotrophic carbon assimilation rates (1.4 µM C d-1) coincided with a pronounced ammonium concentration maximum near the top of the OMZ core. In addition, members of the genus Nitrospina, a dominant nitrite-oxidizing bacteria (NOB) were present suggesting that both ammonia and nitrite oxidation occur at almost undetectable oxygen concentrations. We conclude that the presence of trace oxygen in the OMZ core of this region of the ETNP OMZ is sufficient to support active nitrification.